Hit and run - McDaniel, Lurlene (New York : Delacorte Press, 2007)
Events surrounding the hit and run accident of a popular high school student are told from the viewpoints of those involved, including the victim.
Keywords: Hit and run drivers -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction